Comparative Study on Growth and Conformation of Male Dumbi Lambs under Two Management Systems - Huma Rizwana,; Faizan Shahani,; Rani Abro,; Muhammad Naeem,; Nasir Rajput,; M.I. Memon,; S.H. Abro,; Hassina Baloch,; H.K. Kunbhar,; G.A. Mughal ,; S. Shahzad Ali, (Journal of Basic & Applied Sciences, 2016)
A study was carried out on 12 male lambs of Dumbi sheep breed reared under two management systems at the| department of Livestock Management Faculty of Animal Husbandry and Veterinary Sciences, Sindh Agriculture University Tando jam. The lambs of Dumbi breed were randomly divided into two groups i.e. group A and B (6 lambs in each group). The group A was reared under semi intensive management system (concentrate and open grazing) whereas animals in group B were kept under intensive management system (concentrate and green fodder). The experiment was lasted for (8) weeks and the observations for body weight and body conformation traits (girth, height and length) were recorded on weekly basis. The result indicated that the average body weight of lambs in group A (12.5 kg) was statistically higher (P<0.05) than lambs in group B (11.33 kg). Moreover, the average body conformation of Dumbi lambs of group A in respect of girth, height and length (56.83 and 40.5 cm, 41.5 cm respectively) were significantly higher than (P<0.05) the male Dumbi lambs of group B (55.33 and 39.33 cm, 40 cm respectively). While comparing the economical aspects of lambs reared under two management systems it was noted that the animals of group A were more economical (Rs.337 /lambs) compared to those of group B (Rs.245 /lambs). Result concludes that, the lambs reared under semi intensive management system (concentrate and open grazing) gained more body weight and body conformation than that of lambs reared under intensive management system (concentrate and green fodder).